1996
DOI: 10.2307/1131607
|View full text |Cite
|
Sign up to set email alerts
|

Development of Arithmetical Competencies in Chinese and American Children: Influence of Age, Language, and Schooling

Abstract: The arithmetical competencies of more than 200 Chinese or American kindergarten, first-, second-, or third-grade children were assessed toward the beginning and toward the end of the U.S. school year. All children were administered a paper-and-pencil test of addition skills, a digit span measure, and an addition strategy assessment. The addition strategy assessment provided information on the types of strategies the children used to solve simple addition problems as well as information on the speed and accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
126
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(137 citation statements)
references
References 27 publications
8
126
1
2
Order By: Relevance
“…The speed of number pronunciation influences digit span (i.e., the number of digits than can be retained in short-term memory) and may, in turn, influence people's arithmetic efficiency. Stigler, Lee, and Stevenson (1986) showed that Chinese participants have about a two-digit span advantage over North Americans; and Geary, Bow-Thomas et al (1996) showed that individual differences in digit span influence individual differences in simple arithmetic performance. The ability to retain more digits in short-term memory during calculations may be a factor in the Chinese advantage, especially on these multi-digit problems that require retention of intermediate sums in working memory.…”
Section: Cultural Differences In Strategic Performancementioning
confidence: 99%
“…The speed of number pronunciation influences digit span (i.e., the number of digits than can be retained in short-term memory) and may, in turn, influence people's arithmetic efficiency. Stigler, Lee, and Stevenson (1986) showed that Chinese participants have about a two-digit span advantage over North Americans; and Geary, Bow-Thomas et al (1996) showed that individual differences in digit span influence individual differences in simple arithmetic performance. The ability to retain more digits in short-term memory during calculations may be a factor in the Chinese advantage, especially on these multi-digit problems that require retention of intermediate sums in working memory.…”
Section: Cultural Differences In Strategic Performancementioning
confidence: 99%
“…Working memory in children has been studied in relation to mathematical disabilities (see Geary, 2004, for a review); rather than in relation to its role in normally developing children. As respects strategy selection, higher working-memory spans have been linked with less frequent use of procedural strategies and more frequent use of retrieval strategies (e.g., Barrouillet & Lépine, 2005;Geary, Bow-Thomas, Liu, & Siegler, 1996;Geary, Hoard, Byrd-Craven, &, DeSoto, 2004;Noël, Seron, & Trovarelli, 2004;Steel & Funnel, 2001). Working memory has also been related to strategy eYciency.…”
Section: Evects Of Operation On Arithmetic Strategy Usementioning
confidence: 99%
“…In these studies, boys used direct retrieval and covert strategies (e.g., mental counting) more often than girls did and girls used finger counting and overt strategies (e.g., blocks) more often than boys did. To assess these differences further, Chinese and American kindergarten through third-grade children's use of finger counting and direct retrieval to solve simple addition problems (e.g., 4 ϩ 3) was analyzed using data from several cross-national studies (Geary, Bow-Thomas, Liu, & Siegler, 1996;Geary, Fan, & BowThomas, 1992; see also Geary, 1994). Although the differences were not always statistically significant, in all five samples American girls used finger counting more frequently than did American boys.…”
mentioning
confidence: 99%